Динамика изменений физико-химических показателей виноматериалов при технологической обработке - Бабич, Ирина Михайловна; Гречко, Нина Яковлевна; Бажай-Жежерун, Светлана Андреевна (My University, 2015)
In this master's thesis the effectofliquid enogelatin (home produced) on the quality of wine materials and their permanence is investigated. Enogelatin has higher level of reciprocity with phenolic compounds, increases organoleptic qualities and provides long lasting permanence of drinks, it also has the weak finning ability. The special demand to the manufactured product is its permanence – conditions under which no undesirable changes of physico-chemical and organoleptic qualities appear in wine during the warranty period. These changes are caused by turbidity, mostly colloidal.
Keywords: вино белое сухое; dry white wine; стабилизация вина; wine stabilization; кафедра біотехнології продуктів бродіння і виноробства